Problematika Tanggung Jawab Sosial dan Lingkungan Perusahaan: Perspektif Penyelenggaraan Pemerintahan Daerah dan Hak Asasi Manusia - Nursasmita, Muhammad Akbar (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2024)
The challenge of implementing social and environmental responsibility from a regional government perspective creates its own problems, especially in the context corporate social responsibility which have correlation fulfillment human rights. This research uses normative research methods. The results of this research found that CSR is a concept that continues to develop and finds a balance between companies or business entities that are seeking profit and their responsibilities to society and the environment. Furthermore, the implementation of CSR in the local government faced several problems, such as legal and social. On the other hand, the justification for CSR carried out by business entities can be seen from a human rights perspective, where apart from the state as the holder of obligations, business entities can also play an important role in their obligations towards human rights.Keywords: CSR, Local Government, Human Rights.